INSTAGRAM DAN FENOMENA “JASTIP” DI INDONESIA - Muslicha, Intan Siti; Irwansyah, Irwansyah (Department of Communication Science, Bakrie University, 2019)
Technological advances have now given birth to new media. The information environment arises from the simultaneous and rapidly interconnected Internet evolution of transmission systems, content, quality, and structure of the new media itself. One example of new media is social media, including Instagram. Instagram is now not only an arena for uploading photos but as a means to carry out digital marketing activities. The social media platform has developed as a form of global communication and bridges the relationship between humans and products. As time goes on, a new business model has been born on Instagram. One business model is